2008
DOI: 10.1111/j.1439-0469.2008.00479.x
|View full text |Cite
|
Sign up to set email alerts
|

Sexual size and shape evolution in European newts (Amphibia: Caudata: Salamandridae) on the Balkan Peninsula

Abstract: We used a phylogenetic perspective in an examination of the direction and extent of sexual dimorphism in body size and body shape in European newts from the Balkan Peninsula (alpine newts, Mesotriton alpestris; crested newts, Triturus cristatus superspecies; smooth newts, Lissotriton vulgaris). We found a strong, female-biased sexual size dimorphism (SSD) in the analysed clades of alpine newt, whereas within crested newts we found a less stringent female-biased SSD in Triturus carnifex, Triturus macedonicus an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
31
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 60 publications
1
31
0
Order By: Relevance
“…We cannot say whether this result is due to the different phylogenetic history of the Triturus genus. One of the main cause of nonsignificant differences in digit ratio between sexes can be small sexual size dimorphism in T. cristatus (Ivanović et al, 2008). Another reason could be that crested newts spend more time in water than Lissotriton and Mesostriton.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We cannot say whether this result is due to the different phylogenetic history of the Triturus genus. One of the main cause of nonsignificant differences in digit ratio between sexes can be small sexual size dimorphism in T. cristatus (Ivanović et al, 2008). Another reason could be that crested newts spend more time in water than Lissotriton and Mesostriton.…”
Section: Discussionmentioning
confidence: 99%
“…T. cristatus is more aquatic than other European newt species; moreover, immature crested newts can sometimes be found in water (Jehle et al, 2011;Sparreboom, 2014). In this species differences in body-size between sexes are D2:D4 IN CAUDATA nonsignificant (Ivanović et al, 2008). M. alpestris (the alpine newt), is a medium-sized newt with an unspotted orange belly and throat.…”
Section: Methodsmentioning
confidence: 98%
See 1 more Smart Citation
“…Previous studies revealed that the sexual differences in body size range from female-biased (females larger than males) sexual dimorphism in Ichthyosaura alpestris, more labile SSD in Triturus newts and even male-biased SSD in Lissotriton vulgaris (Malmgrem and Thollesson 1999;Ivanović et al 2008a). In these newts, the relationship between body size and the level of sexual size dimorphism does not follow Rensh's rule (Ivanović et al 2008a), which states that in groups with male-biased SSDs, the sexual dimorphism increases in larger groups (species, races or populations) and on the contrary, in the cases of femalebiased SSD, the intersexual difference diminishes in larger groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…In these newts, the relationship between body size and the level of sexual size dimorphism does not follow Rensh's rule (Ivanović et al 2008a), which states that in groups with male-biased SSDs, the sexual dimorphism increases in larger groups (species, races or populations) and on the contrary, in the cases of femalebiased SSD, the intersexual difference diminishes in larger groups (e.g. Abouheif and Fairbairn 1997).…”
Section: Introductionmentioning
confidence: 99%